P05.87 Hemoglobin level is a relevant prognostic marker of overall survival in primary central nervous system lymphoma: a retrospective study on 160 PCNSL. (19th September 2018) - Le, M; Garcilazo, Y; Younan, N; Houillier, C; Hoang-Xuan, K; Alentorn, A
Abstract: Background: Primary central nervous system lymphomas (PCNSL) are extra-nodal, malignant non-Hodgkin lymphomas of diffuse large B-cell type confined to the CNS or eyes without evidence of systemic spread. PCNSL account for up to 1% of all lymphomas and 3% of primary brain tumors. Despite recent progress in PCNSL treatment, the prognosis remains dismal and there is a medical need to identify novel surrogate markers of the clinical evolution to better tailor their treatment. Recent evidence suggests that routine blood tests like neutrophil-to-lymphocyte ratio (NLR) may be used as an independent prognostic marker in different brain tumors. Therefore, we sought to analyze the impact of different routine blood tests as potential surrogate markers of the clinical evolution of PCNSL. Material and Methods: A retrospective cohort of PCNSL treated at Pitié-Salpêtrière Hospital from 2011 to 2018 with available clinical data follow-up and routine blood before high-dose methotrexate based chemotherapy. We have analyzed the impact of NLR, neutrophil-to-platelets and hemoglobin levels to overall survival using univariate and multivariate analysis by Cox proportional hazards ratio regression. Results: We identified 160 PCNSL. The median age was 67 years [Interquartile range, IQR 59–75], median neutrophil was 6595/mm 3 [IQR 4790–7275], lymphocyte 1740/mm 3 [IQR 1290–2603], platelets 231000/mm 3 [IQR 194000–277000] and hemoglobin 13.5g/dL [IQR 12.3–14.4]. Interestingly, in this cohort NLR, NPR and platelets levels were not related with overall survival (OS) p-value > 0.05. However, Hemoglobin level (cut-off median) was strongly associated with OS in univariate (log-rank p-value < 0.001). In addition this result was also confirmed in the multivariate analysis after adjusting by age and Karnofsky Performance Status, (HR 0.46 CI 95% 0.29–0.73, p-value < 0.001). Conclusion: In this retrospective monocentric study, the Hemoglobin level at diagnosis before starting high-dose methotrexate based chemotherapy was strongly associated with OS in PCNSL. We are currently validating these results in two prospective multicentric cohorts of PCNSL to further corroborate this potential easy-to-use clinical marker in PCNSL.